2021
DOI: 10.3390/genes12040584
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Loci and Candidate Genes for Resistance to Powdery Mildew in a Resequenced Cucumber Germplasm

Abstract: Powdery mildew (PM) is one of the most serious diseases in cucumber and causes huge yield loss. Multiple quantitative trait loci (QTLs) for PM resistance have been reported in previous studies using a limited number of cucumber accessions. In this study, a cucumber core germplasm (CG) consisting of 94 resequenced lines was evaluated for PM resistance in four trials across three years (2013, 2014, and 2016). These trials were performed on adult plants in the field with natural infection. Using genome-wide assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…SNP Lalb_Chr05_3706534 is located in the non-coding region of Lalb_Chr05g0217341. Homologs of Lalb_Chr05g0217341 in closely related legume species encode for paired amphipathic helix protein Sin3-like 4 proteins, which are known to be involved in powdery mildew ( Podosphaera fusca ) resistance in cucumber (Liu et al 2021 ). SNP Lalb_Chr05_3784474 is considered linked to Lalb_Chr05_3706534 and is located within the gene Lalb_Chr05g0217471 which encodes a LRR containing receptor-like protein with a serine/threonine kinase.…”
Section: Discussionmentioning
confidence: 99%
“…SNP Lalb_Chr05_3706534 is located in the non-coding region of Lalb_Chr05g0217341. Homologs of Lalb_Chr05g0217341 in closely related legume species encode for paired amphipathic helix protein Sin3-like 4 proteins, which are known to be involved in powdery mildew ( Podosphaera fusca ) resistance in cucumber (Liu et al 2021 ). SNP Lalb_Chr05_3784474 is considered linked to Lalb_Chr05_3706534 and is located within the gene Lalb_Chr05g0217471 which encodes a LRR containing receptor-like protein with a serine/threonine kinase.…”
Section: Discussionmentioning
confidence: 99%
“…The single recessive gene Csa5M622830 , which encodes a GATA transcriptional factor, is likely the gene for the complete PM resistance introgressed from Cucumis hystrix ( Zhang et al, 2018 ). CsGy5G015660 , which encodes a putative leucine-rich repeat receptor-like serine/threonine-protein kinase, is currently considered a strong candidate gene for PM resistance in cucumber ( Liu et al, 2021 ; Zhang C. et al, 2021 ). Moreover, proteins related to PM resistance have also been identified and functionally verified.…”
Section: Inheritance Quantitative Trait Loci Mapping and Candidate Ge...mentioning
confidence: 99%
“… Call et al (2012b) identified three highly DM-resistant materials, PI 197088, PI 330628, and PI 605996, from 1,300 cucumber collections. Among them, PI 197088 is the most studied for DM resistance, with multiple genes being controlled in breeding programs ( Li et al, 2018 ; Liu et al, 2021 ). PI 197088 also has high resistance to PM.…”
Section: Inheritance Quantitative Trait Loci Mapping and Candidate Ge...mentioning
confidence: 99%
See 1 more Smart Citation
“…Cucumber plants have multiple mechanisms to resist fungal infections, and the interactions between cucumbers and PM fungi are strongly influenced by resistance genes. While previous studies have confirmed that cucumber PM resistance is controlled by multiple resistance loci, most of these studies have been limited to quantitative trait locus mapping ( Shen, 2009 ; Yu, 2015 ; Wang et al, 2020 ; Liu et al, 2021 ). At present, only a few recessive resistance genes, mainly including Mildew Resistance Locus O ( MLO ) and NBS-LRR -type resistance gene families, have been successfully cloned and validated ( Nie et al, 2015 ; Shi, 2016 ; Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%